ROLE OF KHURSHIDBANU NATAVAN IN THE FORMATION OF THE KARABAKH LITERARY MEDIA IN THE 19th CENTURY - Zenfira M. Aslan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In the second half of the 19th century, Khurshidbanu Natavan (1832-1897), known as the “Khan gizi” (the khan’s daughter), played a significant role in the formation of the literary environment of Karabakh. Her literary activities, serious participation in the artistic and cultural life of the region gave impetus to the development of the cultural life of Shusha and the whole Karabakh. Majlis-i Uns (“Gathering of Friends”) literature society continued its work thanks to her hard work. A special role was played by the works of Khurshidbanu Natavan, based on the traditions of divan literature, and influencing the revival of the literary environment in Karabakh. The poems “I am crying”, “Regrets”, “Don’t go away”, “Without you”, “A carnation”, “I wish it were”, “I am dying,” “Bulbul”, “Well, doesn’t come”, and other poetic works introduced great interest in the literary environment. Poets wrote imitations to them – poems-nezira. In this article, the object of analysis in the literary environment context of Karabakh of the 19th century is the artistic work of Khurshidbanu Natavan. Here is described the basic principles of her literary work, the main factors affecting the essence of her work. Particularly, the author draws a parallel between the works of Fizuli and Natavan and substantiates the profound influence of the poetic thinking peculiarities of the brilliant poet of the Middle Ages and Natavan. The poetic works of Khurshidbanu Natavan, based on the traditions of divan literature, played a distinctive role in the revival of the literary environment of Karabakh in the 19th century. It should be noted that Natavan began her creative activity in the 50s of the 19th century. The first poetic works that brought popularity to Khurshidbani, with some exceptions, did not survive today. There is enough information about the later period of the author’s work, after the seventies, signed by the pseudonym “Natavan”. Gazelles, written over the past few years of poetry, are fascinating in their profound content, simplicity of style and originality. An important part of Natavan gazelles is the chanting of love. In love poems, the traditional theme is expressed in a new form, a different style. The author’s gazelles attract attention with their deep lyricism. These gazelles, which are a high artistic expression of pure and sincere feelings, are a lyrical reflection of the treasury of creativity of the artist of the word, possessing deep spirituality. Love expressed in a poem is not a product of abstract feelings and thoughts, it is a poetic expression of real feelings associated with life.